Atmosphere and Climate Studies by Occultation Methods - Foelsche, Ulrich; Kirchengast, Gottfried; Steiner, Andrea (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Since the early use of the occultation measurement principle for sounding pla- tary atmospheres and ionospheres, its exploitation in atmospheric remote sensing has seen tremendous advances. In this book we focus on sensors on Low Earth Orbit (LEO) satellites, which exploit solar, lunar, stellar, GNSS (Global Navi- tion Satellite Systems), and LEO-crosslink signals for observing the Earth's - mosphere and climate. The methods all share the key properties of self-calibration, high accuracy and vertical resolution, global coverage, and (if using radio signals) all-weather ca- bility. The atmospheric parameters obtained extend from the fundamental va- ables temperature, density, pressure and water vapor via trace gases, aerosols and cloud liquid water to ionospheric electron density. Occultation data are therefore of high value in a wide range of fields including climate monitoring and research, atmospheric physics and chemistry, operational meteorology, and ionospheric physics. nd The 2 International Workshop on Occultations for Probing Atmosphere and Climate - OPAC-2 - was held September 13-17, 2004, in Graz, Austria. OPAC-2 aimed at providing a casual forum and stimulating atmosphere fertilizing scientific discourse, co-operation initiatives, and mutual learning and support amongst members of all different occultation communities. The workshop was attended by 40 participants from 12 different countries who actively contributed to a scientific programme of high quality and to an excellent workshop atmosphere, which was judged by the participants to have fully met the aims expressed.